Colony-forming unit cell (CFU-C) assays at diagnosis: CFU-G/M cluster predicts overall survival in myelodysplastic syndrome patients independently of IPSS-R - Li, Bing; Liu, Jinqin; Qu, Shiqiang; Gale, Robert Peter; Song, Zhen; Xing, Ruixian; Liu, Junxia; Ren, Yansong; Xu, Zefeng; Qin, Tiejun; Zhang, Yue; Fang, Liwei; et al. (Oncotarget, 2016)
In vitro colony-forming unit cell (CFU-C) assays are usually-used to detect the quantitative and qualitative features of haematopoietic stem cells (HSCs). We studies CFU-C assays in bone marrow samples from 365 consecutive subjects with newly-diagnosed myelodysplastic syndrome (MDS). Data were interrogated for associations with prognosis. CFU-C assays were performed according to the protocol of MethoCultTM H4435 Enriched. 365 consecutive newly-diagnosed, untreated subjects with MDS diagnosed from July, 2007 to April, 2014 were studied. All subjects were reclassified according to the 2008 WHO criteria. Subjects were observed for survival until July 31, 2015. Follow-up data were available for 289 (80%) subjects. Median follow-up of survivors was 22 months (range, 1-85) months. Erythroid and myeloid colonies were isolated from each subject with one cytogenetic abnormality such as del(5/5q), +8, del(7/7q) or del(20q). Cytogenetic abnormalities of each colony were analyzed by fluorescence in situ hybridization (FISH). SPSS 17.0 software was used to make statistical analysis. The numbers of burst-forming units-erythroid (BFU-E), colony forming unit-erythroid (CFU-E) and colony forming unit-granulocytes/macrophages (CFU-G/M) were significantly lower than normals. A high ratio of cluster- to CFU-G/M was associated with poor-risk cytogenetics. In multivariable analyses a cluster- to CFU-G/M ratio >0.6 was an independent risk-factor for OS after adjusting for IPSS-R (HR 3.339, [95%CI 1.434-7.778]; P = 0.005) in very high-risk cohort. These data suggest abnormalities of proliferation and differentiation of erythroid and myeloid precursor cells in vitro parallel the ineffective hematopoiesis typical of MDS and may be useful in predicting outcomes of persons with higher-risk MDS.